Nanoporous Substrate-Infiltrated Hydrogels: a Bioinspired Regenerable Surface for High Load Bearing and Tunable Friction - Ma, Shuanhong; Scaraggi, M.; Wang, Daoai; Wang, Xiaolong; Liang, Yongmin; Liu, Weimin; Dini, Daniele; Zhou, Feng (Advanced functional materials, 2015)
Nature has successfully combined soft matter and hydration lubrication to achieve ultralow friction even at relatively high contact pressure (e.g., articular cartilage). Inspired by this, hydrogels are used to mimic natural aqueous lubricating systems. However, hydrogels usually cannot bear high load because of solvation in water environments and are, therefore, not adopted in real applications. Here, a novel composite surface of ordered hydrogel nanofiber arrays confined in anodic aluminum oxide (AAO) nanoporous template based on a soft/hard combination strategy is developed. The synergy between the soft hydrogel fibers, which provide excellent aqueous lubrication, and the hard phase AAO, which gives high load bearing capacity, is shown to be capable of attaining very low coeffcient of friction (<0.01) under heavy load (contact pressures ≈2 MPa). Interestingly, the composite synthetic material is very stable, cannot be peeled off during sliding, and exhibits desirable regenerative (self‐healing) properties, which can assure long‐term resistance to wear. Moreover, the crosslinked polymethylacrylic acid hydrogels are shown to be able to promptly switch between high friction (>0.3) and superlubrication (≈10−3) when their state is changed from contracted to swollen by means of acidic and basic actuation. The mechanisms governing ultralow and tunable friction are theoretically explained via an in‐depth study of the chemomechanical interactions responsible for the behavior of these substrate‐infiltrated hydrogels. These findings open a promising route for the design of ultra‐slippery and smart surface/interface materials. A novel composite surface of ordered nanohydrogel arrays confined in an anodic aluminum oxide template based on a soft/hard combination strategy is reported. The surface shows a low friction coefficient (<0.01) under 40 N and contact pressures of ≈2 MPa, along with desirable regenerative and antiwear properties, while exhibiting smart switching between high friction (>0.3) and superlubrication (≈10−3) by acidic and basic actuation.